Clinical relevance of RNA editing profiles in lung adenocarcinoma - Shi, Si; Chen, Shibin; Wang, Menghang; Guo, Bingchen; He, Yaowu; Chen, Hong (Frontiers in Genetics, 2023)
Background: Lung adenocarcinoma (LUAD) is the most common occurring lung cancer worldwide with increasing death rates. Growing evidence has demonstrated the significance of RNA editing dysregulation in cancer. The aim of the present study was to evaluate RNA editing events that might be clinically useful or tumorigenic. Methods: To explore survival-related RNA editing events in LUAD, its RNA editing profiles, gene expression data, and corresponding patients’ clinical information were downloaded from the Cancer Genome Atlas (TCGA) and the synapse database. The next step was to select prognostic RNA editing sites, using a univariate Cox analysis. We evaluated 10441 RNA editing sites (P < 0.001) and patients were randomly divided into a validation cohort (n = 176) and a training cohort (n = 264). Cox proportional hazards regression and lasso regression analysis were used to determine survival-related RNA editing sites, create risk ratings for those sites and build a prognostic model and a nomogram for assessing overall survival (OS). The "Pheatmap" program was used to create risk curves that included risk score, survival time, and expression of RNA editing.The decision curve analysis and the 1-, 2-, and 3-year corrective curves were simultaneously used to evaluate the nomogram. We also evaluated the relationship between the amount of RNA editing and host gene expression and the impact of RNA editing on transcriptome expression. Results: PGPEP1|chr19:18476416, ANKRD36BP1 (dist = 3795), TBX19 (dist = 29815)|chr1:168220463 (P < 0.001), SNTB2|chr16:69338598, HOOK3|chr8:42883441, NDUFV3|chr21:44329452, and FKBP11|chr12:49316769 were used in the prognostic model construction. High levels of risk score were significantly associated with worse OS and progression-free survival. Tumour stage and risk score were related to OS in LUAD patients. The predictors were among the prognostic nomogram model's risk score, age, gender, and tumor stage. The level of RNA editing was markedly elevated in tumor tissues and was highly variable between patients. Conclusions: Events involving RNA editing in LUAD were highly functional and clinically relevant. The RNA editing-based model provides a solid framework for further investigation of the functions of RNA editing in non-coding areas and may be used as a unique method for predicting LUAD survival.